OCT1 Deficiency Affects Hepatocellular Concentrations and Pharmacokinetics of Cycloguanil, the Active Metabolite of the Antimalarial Drug Proguanil - Matthaei, Johannes; Seitz, Tina; Jensen, Ole; Tann, Annabelle; Prukop, Thomas; Tadjerpisheh, Sina; Brockmöller, Jürgen; Tzvetkov, Mladen V (Clinical pharmacology and therapeutics, 2019)
Cycloguanil, the active metabolite of proguanil, acts on malaria schizonts in erythrocytes and hepatocytes. We analyzed the impact of the organic cation transporter OCT1 on hepatocellular uptake and pharmacokinetics of proguanil and cycloguanil. OCT1 transported both proguanil and cycloguanil. Common variants OCT1*3 and OCT1*4 caused a substantial decrease and OCT1*5 and OCT1*6 complete abolishment of proguanil uptake. In 39 healthy subjects, low-activity variants OCT1*3 and OCT1*4 had only minor effects on proguanil pharmacokinetics. However, both, cycloguanil area under the time-concentration curve and the cycloguanil-to-proguanil ratio were significantly dependent on number of these low-functional alleles (P = 0.02 for both). Together, CYP2C19, CYP3A5, OCT1 polymorphisms, and sex accounted for 61% of the variation in the cycloguanil-to-proguanil ratio. Most importantly, in vitro OCT1 inhibition caused a fivefold decrease of intracellular cycloguanil concentrations in primary human hepatocytes. In conclusion, OCT1-mediated uptake is a limiting step in bioactivation of proguanil, and OCT1 polymorphisms may affect proguanil efficacy against hepatic malaria schizonts.